Analisis Karakterisasi Penyakit pada Tanaman Pisang Menggunakan Kamera Termal dengan Metode Tresholding - Elka Pranita (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
Abstract Banana is a fruit plant that is widely produced in Indonesia. Unfortunately, this plant is verysusceptible to diseases which can reduce the quality and quantity of the crop. This paper proposes diseasedetection in banana plants using a thermal camera. The detection is carried out using image processingtechniques with multilevel thresholding methods. The image is captured using a thermal camera, then theimage is preprocessed to suit what is desired. After that, so that the position is the same as the image takenusing a digital camera, the image produced by the thermal camera is carried out by an image registrationprocess. The image processing result is compared with the ground truth image obtained from a digitalcamera to determine the effectiveness of the proposed method. The effectiveness of the proposed method ismeasured using the parameters Recall, Precision, F-measure, and Accuracy. The effectiveness of theproposed method is effective enough to produce a recall value of 76.65 percents, Precision 58.38 percents, F-measure64.68 percents, and Accuracy 62.87percents. Keywords Banana Plant Disease, Thermal Image, RGB Image, Multi Thresholding, EffectivenessMeasurement.